Lineamientos de inspección de seguridad vial en entornos escolares para el desarrollo de un plan de seguridad vial en su componente de infraestructura para las Instituciones Educativas oficiales municipales IEOM (preescolar, básica y media), estudio de caso: municipio de Chía Cundinamarca (2018)
The official educational institutions (OEI) are places where children and young people can fully develop and, therefore their environment should provide welfare and safety. For this, it is necessary that the municipal authorities and other actors who work in these areas, as professionals and the educational community in general, get involved through the implementation of healthy school policies, that promote appropriate physical environments and spaces of emotional and social well-being. This document characterizes the official educational environments of the municipality of Chía, which includes an analysis of the practices that public schools must develop to promote safe and healthy school environments, in addition, makes a qualitative approach to a case study, through documentary analysis (educational legislation and analysis of institutional documents) and semi-structured interviews to managers, students and professors of the participating OEI. The analyzed guidelines show that security as well as physical, emotional and social health are considered in the operation of educational centers. In addition, there is coherence between the content of educational legislation, institutional documents and what is implemented in the centers through programs, projects and daily actions. Finally, an audit of road safety was carried out as a case study at the OEI San Jose María Escriva de Balaguer in Chía, where the problems related to road safety in the area of the educational institution were diagnosed, with the objective of implementing the road safety guidelines in school environments as a public policy by the Municipality of Chía.